Effects of prebiotics on the fermentation of traditional suancai of Northeast China - Mingwei Zhao; Xinying Cao; Yuzheng Wu; Sibo Zou; Zhigao Li; Xinping Lin; Chaofan Ji; Liang Dong; Sufang Zhang; Chenxu Yu; Huipeng Liang (Food Science and Human Wellness)
Suancai is a traditional fermented vegetable widely consumed in Northeast China. In this study, different prebiotics were used to improve the quality of suancai. Four prebiotics (inulin (INU), xylooligosaccharide (XOS), galactooligosaccharide (GOS), and stachyose (STA)) were shown to reduce the pH value and increase the content of total titratable acidity (TTA) in suancai, while the contents of most organic acids were also increased. The addition of prebiotics had significant effects on the bacterial microbiota during the suancai fermentation process. All prebiotics were shown to contribute to the growth of Lactobacillus. The suancai sample with fructooligosaccharides (FOS) had the highest relative abundance of Lactobacillus. Besides, INU and XOS could increase the abundance of Weissella. To evaluate the quality of suancai fermented with prebiotics, profiles of volatile flavor compounds (VOCs) and free amino acids (FAA) were analyzed. The prebiotics affected the VOCs and FAA profiles via transforming the bacterial microbiota. In addition, the addition of prebiotics also changed the taste prof iles of the suancai samples. This study is among the first attempts to reveal the effects of different prebiotics on suancai fermentation, and the findings provide a foundation to develop new ways for improving the quality of suancai.